IMPLEMENTASI PENINGKATAN RETRIBUSI PELAYANAN PASAR - Wijaya E.01109007, Gusti Surya (FISIP Universitas Tanjungpura, 2013)
The problem in my research that the seller donâ€™t extend â€œsurat penunjukan tempat usahaâ€ (SPTU)Â countinely each year. There isnâ€™tÂ penalty for the seller who arenâ€™t pay the retribution, the service and facility isnâ€™t conducive for them. They are paying the retribution but they havenâ€™t had the good facilities in the market. The consequent for bad facility and service that made some of the seller didnâ€™t want to pay it. The problem is coming from Dinas Perindustrian dan Perdagangan Koperasi dan UKM Pontianak in the way to increase market service retribution havenâ€™t yet improving retribution, for example : some of identified havenâ€™t inventory in object retribution and increasing the quality ofÂ human resources retribution officer. The result is showing that the context of policy consist of authority benefid and strategic muolved unscrupulous person, institution characteristic, obedience to the authorities and officer responsiveness. The research result is showing fundamental factor market service retribution didnâ€™t reach target due to collusion in estabilisment retribution market service collection, some of the seller reluctense to pay it, mental attitude, discipline, motivation and understanding duties, subject and function which is still low. The chaiman of the department must dealing with phenomena and giving motivation to the officer with presenting reward to the officer good achiever by compliment and promotion, firm sanction to officer who breach through cut incentive, decrease the value DP-3, termination of employment or other sanction to enchancing officer discipline, direction, about main job and function to each employee in various, ceremony, department meeting, evaluation meeting and other occasions.Â Keywords: Implementation, retribution , market service